Social Determinants of Health Associated with Self-Reported HIV Testing among Women. - Shahab Rezaeian; Nader Esmailnasab (Tehran University of Medical Sciences, 2013)
There currently is lack of knowledge about HIV testing practices in Iran. The purpose of this pilot study was to evaluate the prevalence of self-reported HIV testing and its associated factors among women.This cross-sectional study was conducted in Sanandaj City, located in the west of Iran, in 2012. Data were collected using self-administered questionnaire including demographics characteristics and the main outcome variable was self-reported HIV testing. The univariate and multivariate logistic regression models using STATA software was used for data analysis.A total of 1200 women were interviewed during the study (Response rate=87.5%). The mean age was 29.67 years (SD: 7.01 years), 49% were aged 28 years or younger, 39.2% were single, 16.9% were pregnant and 60% did not have academic education. The proportion of women that were HIV-tested was, 32.1% (CI 95%: 29.2%, 35.0%). HIV testing was associated with younger age, knowledge of HIV/AIDS, household wealth, pregnancy, academic education, occupation and duration time of occupation, rating of quality of health services and substance use history in her husband.The self-reported HIV testing rate among our sample women is 32.1%, lower than the HIV testing rate in other studies. Therefore, interventions to expand HIV testing and increase awareness of HIV risk are urgently needed in Iran.